Financial Inclusion Towards Financial Stability in Ghana: Insights from Quantile Regression Analysis - Narh, Philomina Maku; Dzitse, Collins Dodzi (Copernican Journal of Finance & Accounting, 2025)
In Ghana, only 52.7% of the population is fully financially included in the formal financial system. However, while financial inclusion is often linked to economic resilience and stability, as it can broaden access to financial services and reduce vulnerability, its direct, quantifiable impact, particularly at different quantile levels, remains largely untested in the sub-Saharan African context. This study addresses this gap by employing quantile regression analysis to examine the impact of financial inclusion on Ghana’s financial stability, using time-series data from 2005 to 2021. The results show significant cointegration between the variables, indicating that the independent variables act as long-run forcing factors for financial stability. The long-run analysis shows that financial inclusion positively affects financial stability, especially at higher quantiles. These findings highlight the need to consider various quantile levels in national financial assessments. The study suggests prioritizing financial inclusion during periods of low financial stability because of its positive correlation with strengthening a country’s financial landscape, which can aid in economic resilience and sustainability in Ghana and many sub-Saharan African countries.